Représentation de l’espace et du temps dans le modèle situationnel construit par un lecteur - Yves Bestgen (Discours)
For more than twenty years, one of the major challenges faced by psycholinguistics has been to describe the nature of the mental representation a reader builds. This question has been studied for so many years because, contrary to other processes like lexical access or syntactic analysis, the comprehension of a text was long considered to be difficult to study scientifically as its definitions were not sufficiently rigorous. Today this is no longer the case. Researchers agree to define the comprehension of a text as the construction of a situation model which combines the propositions extracted from the text with those reactivated in long-term memory. This situation model is a representation of what the text is about, not of the text itself. Among the multiple dimensions supposedly represented in the situation model, space and time has aroused the most interest. The main objective of this paper is to confront our knowledge concerning the role of these two dimensions during the construction of the situation model in order to propose new hypotheses regarding the impact of spatial adverbials on this process. A second and equally important objective is determining how the conclusions resulting from empirical research about space and time fit in with the two main views describing the cognitive processes underlying comprehension: the constructivist and the memory-based views.